PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TGT BERORIENTASI PADA PAKEM UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PKN SISWA KELAS V SDN JEJANGKIT MUARA 2 - Agustina, Rahidatul Laila (Meretas: Jurnal Ilmu Pendidikan, 2017)
This study aims to improve the activity and student learning outcomes in Civics subject in particular organization of matter using cooperative learning model oriented AJEL TGT. This study was conducted at Muara Jejangkit SDN 2 in 2013/2014 academic year. Subjects in this study were fifth grade students totaling 14 people. Type of research is Classroom Action Research (CAR), is collaboration. Data collection techniques used were interviews, observation and tests. Based on the results of data analysis, student activity from cycle I to cycle II always show improvement with an indication of a growing number of students doing activities as mentioned in the specified indicators. Learning outcomes was also an increase in the evaluation of the first cycle in which the classical completeness obtained amounted to 64% (8 people) with an average of 70.9 learning outcomes increased by 29% to 93% (13 people) and the class average increased to 81 , 6. It can be concluded that the application of cooperative learning model oriented TGT AJEL can increase activity and student learning outcomes in Civics in SDN Jejangkit Muara 2 2013/2014 school year. It is recommended for the holding of further research with these steps: (1) Manage your time carefully so that the implementation of learning as planned, (2) Students should not be ashamed to ask about the materials that are considered difficult to other friends, (3) before the start of the lesson should remind back previous learning materials through the questions.